AlNxOy thin films deposited by DC reactive magnetron sputtering - Borges, Joel Nuno Pinto (2010)
AlNxOy thin films were produced by DC reactive magnetron sputtering, using an atmosphere of argon and a reactive gas mixture of nitrogen and oxygen, for a wide range of partial pressures of reactive gas. During the deposition, the discharge current was kept constant and the discharge parameters were monitored. The deposition rate, chemical composition, morphology, structure and electrical resistivity of the coatings are strongly correlated with discharge parameters. Varying the reactive gas mixture partial pressure, the film properties change gradually from metallic-like films, for low reactive gas partial pressures, to stoichiometric amorphous Al2O3 insulator films, at high pressures. For intermediate reactive gas pressures, sub-stoichiometric AlN x O y films were obtained, with the electrical resistivity of the films increasing with the non metallic/metallic ratio.